Feeding Ethology of the Domestic Dog (Canis familiaris) Correlates with the Phenomenon of Classical Conditioning - Baruah, Jimi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Aim: Feeding ethology of Canis familiaris is closely related to their overall health and wellbeing. Domestic dog (Canis familiaris) acquire behaviors, attitudes, ideas and new knowledge through the process of learning. This learning can occur through both conscious and unconscious pathways. One of those unconscious methods of learning in case of Canis familiaris is classical conditioning. It is a learning process in which learning occurs by association. It is a process of learning in which an automatic, conditioned response is paired with a specific stimuli and the dog’s innate reflexes are conditioned to react to subtle signals. Over time, the dog learns to associate the subtle signal with the specific event. This phenomenon has been well-illustrated in the Pavlov’s experiment. Conclusion: The unconditioned response in this experiment was the dog salivating for food and the conditioned stimulus was the stimulus that can eventually trigger a conditioned response. In this case, the conditioned stimulus was the ringing of the bell for the dog to have its food and the conditioned response was the salivation caused in the dog. Eventually, the dog could associate the ringing of the bell with the food and would salivate at the sound of the bell alone. However, classical conditioning describes how environmental stimuli such as advertisements of food can activate physiological and psychological responses in a dog causing cravings for food and increased salivation. Thus the body of Canis familiaris adapts itself to the given conditioned reflex and expects food exactly at the same time everyday.